The development of a circuit training model based on articulate storyline for grassroot age in soccer games - Prisca Widiawati; Fahrial Amiq; Muhammad Hamzah Pratama; Dinda Arisetya Purwadi; Yulingga Nanda Hanief; I Made Satyawan (Universitas Negeri Malang, 2023)
Background: The field of training, particularly soccer, has been driven to integrate technology into the training process due to growing demands in the digital era. Objective: The aim of this study was to develop a circuit training product for grassroots soccer players. This product was presented in the form of interactive media using an articulate storyline. Methods: The research method employed in this study is an adaptation of the research and development method model initially introduced by Lee & Owens in 2004. It comprises the stages of needs analysis and initial to final analysis, design planning, product development, implementation of development results, and evaluation of the achievement of development goals. Results: Moreover, it could be concluded that this articulate storyline-based circuit training product met very excellent criteria and is appropriate for usage by athletes in the training process after it underwent validation by a coaching expert, a soccer expert, small group trials, and field testing. Conclusion: It was intended that this development would serve as a guide for soccer coaches in mentoring athletes, particularly those at grassroot age.